2020
DOI: 10.1111/nph.16562
|View full text |Cite
|
Sign up to set email alerts
|

Beyond natural: synthetic expansions of botanical form and function

Abstract: Summary Powered by developments that enabled genome‐scale investigations, systems biology emerged as a field aiming to understand how phenotypes emerge from network functions. These advances fuelled a new engineering discipline focussed on synthetic reconstructions of complex biological systems with the goal of predictable rational design and control. Initially, progress in the nascent field of synthetic biology was slow due to the ad hoc nature of molecular biology methods such as cloning. The application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 153 publications
0
28
0
Order By: Relevance
“…It has also been shown that using contemporary synthetic biological parts is also possible in bryophytes (Peramuna et al, 2018). The use of mosses and liverworts has recently been reviewed in several papers (Ishizaki et al, 2016;Yongabi Anchang and Simonsen, 2019;Decker and Reski, 2020;Patron, 2020).…”
Section: Metabolic Engineering In Bryophytesmentioning
confidence: 99%
“…It has also been shown that using contemporary synthetic biological parts is also possible in bryophytes (Peramuna et al, 2018). The use of mosses and liverworts has recently been reviewed in several papers (Ishizaki et al, 2016;Yongabi Anchang and Simonsen, 2019;Decker and Reski, 2020;Patron, 2020).…”
Section: Metabolic Engineering In Bryophytesmentioning
confidence: 99%
“…Secondly, by engineering previously characterized biological components into novel configurations with predicted behaviors, such as the creation of genetic circuits ( Sprinzak and Elowitz, 2005 ; Antunes et al, 2006 , 2011 ; Khakhar et al, 2018 ), we can test and refine our understanding of these components and the broader cellular and organismal context they operate in. These two approaches have led to some major breakthroughs in understanding microbial ( Sprinzak and Elowitz, 2005 ) and mammalian biology ( Mathur et al, 2017 ) and can be applied to diverse biological systems, including plants ( Patron, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of synthetic biology approaches to engineering plant systems has facilitated advances in the control and expression of biosynthetic pathways, enabling plants as an alternative production chassis (Patron 2020;Stephenson et al 2020). A relative of tobacco, Nicotiana benthamiana (Bally et al 2018;Goodin et al 2008) has emerged as a favoured species for plantbased production of pharmaceutical proteins (Lomonossoff and D'Aoust 2016) and metabolic pathway reconstitution (Stephenson et al 2020).…”
Section: Introductionmentioning
confidence: 99%